Brachial Neuritis After Botulinum Toxin Injections for Cervical Dystonia: A Need for a Reappraisal? - Cani, Ilaria (Mov Disord Clin Pract, 2018)
BACKGROUND: Brachial neuritis has previously been described as a rare occurrence in patients receiving botulinum toxin for cervical or writing/focal arm dystonia. METHODS: We report four cases of patients with a long history of cervical dystonia treated with botulinum toxin injections. RESULTS: All patients developed pain and muscular weakness around the shoulder, with EMG studies suggesting brachial neuritis. CONCLUSIONS: In the context of these observations, we discuss the question of an association between brachial neuritis and botulinum toxin treatment.